2016
DOI: 10.1007/s00018-016-2401-0
|View full text |Cite
|
Sign up to set email alerts
|

Multi-OMIC profiling of survival and metabolic signaling networks in cells subjected to photodynamic therapy

Abstract: Photodynamic therapy (PDT) is an established palliative treatment for perihilar cholangiocarcinoma that is clinically promising. However, tumors tend to regrow after PDT, which may result from the PDT-induced activation of survival pathways in sublethally afflicted tumor cells. In this study, tumor-comprising cells (i.e., vascular endothelial cells, macrophages, perihilar cholangiocarcinoma cells, and EGFR-overexpressing epidermoid cancer cells) were treated with the photosensitizer zinc phthalocyanine that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 78 publications
2
24
0
Order By: Relevance
“…These results are in line with a previous report demonstrating that at LD 50 , a lipophilic phthalocyanine PS localizing to mitochondrial membranes, caused a time-dependent loss of metabolic activity and viability within a 24 period after illumination [ 11 ]. The authors concluded that reactions leading to suppression of metabolism and activation of cell death pathways progressed for at least 24 h after PDT [ 11 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in line with a previous report demonstrating that at LD 50 , a lipophilic phthalocyanine PS localizing to mitochondrial membranes, caused a time-dependent loss of metabolic activity and viability within a 24 period after illumination [ 11 ]. The authors concluded that reactions leading to suppression of metabolism and activation of cell death pathways progressed for at least 24 h after PDT [ 11 ].…”
Section: Resultssupporting
confidence: 93%
“…Since dead cells detach and are removed with the medium before fixation, SRB stains only viable, attached cells. SRB staining is thus considered a suitable method to estimate fully executed cell death [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal cancer has high morbidity and mortality, partly because patients tend to be diagnosed at an advanced stage and with esophageal obstruction, which seriously affects their quality of life. Thankfully, an effective medical treatment, PDT, has been found to relieve the esophageal obstruction by inducing localized tumor destruction via the photochemical generation of cytotoxic singlet oxygen [15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…These studies provide more information on the pathogenic pathways, but they are all based on a single omics platform and cannot reveal the links for the components of signaling pathways at transcript, protein and metabolite levels. Given that many signaling pathways are orchestrated by global networks that cut across multiple omics layers [ 10 ], the researchers have recently begun to integrate the multi-omics data measured in a certain experiment to give a much more detailed view of signaling pathways than when applied individually [ 11 13 ]. However, to date no researcher has comprehensively integrated these diverse sets of data to study SLE.…”
Section: Introductionmentioning
confidence: 99%